JUAL BELI OLI BEKAS DALAM TINJAUAN HUKUM EKONOMI SYARIAH (Studi di Jorong Saruaso Barat Nagari Saruaso) - Taufik Hidayat; Saadatul Maghfira (Jurnal Integrasi Ilmu Syariah (Jisrah), 2021)
The author's research is that first, the practice of buying and selling oil that has been used before has occurred in Nagari Saruaso, Tanjung Emas sub-district, has been going on for a long time, that used oil from consumers is not used anymore or is no longer needed by consumers, so the used oil is left in the workshop. then the motorcycle repair shop collects used oil in a container or drum. The used oil is resold by the workshop to used oil collectors. Second, from the Sharia Economic Law review that the activity of buying and selling used oil at a motorcycle repair shop in Jorong Saruaso Barat, Nagari Saruaso is declared invalid, because the owner of the workshop is not the legal owner of the used oil, but it can be legal if there are pillars of buying and selling, namely ijab (an expression of buying from a buyer) and qabul (an expression of selling and selling).